Impact of pre-sowing red laser irradiation of corn seeds on quality and quantity of harvest yield - de Jesus Rivera-Talamantes, Carlos Francisco; Gonzalez-Lopez, Gabriela; Michtchenko, Alexandre; Juan Carlos Suarez-Calderon (Emirates Journal of Food and Agriculture, 2023)
As the population increases, more people need to be fed. In order to find a physical method that influence the corn production, this work is dedicated to evaluating the impact of pre-sowing red laser irradiation of corn (Zea mays L.) seeds on harvest yield. The aim was to analyze the influence of red laser radiation on corn seeds, on the quantity and quality of yield, on large-scale and open field production. It is hypothesized that at least one red laser irradiation treatment could improve corn crop yield. In radiation, a red laser diode at 660 nm with a power of 100 mW was used, two radiation densities were used (D1: 2 mW cm-2 and D2: 4 mW cm-2), applied during 4 exposure times (T1: 15, T2: 30, T3: 60 and T4: 120 s) and a control group without treatment (C). A random arrangement was used, in a 2 x 4 factorial scheme, totaling 8 treatments and control, with four replications. The data were subjected to an ANOVA and the means were compared with the Tukey test (HSD; p ≤ 0.05). The D2-T4 treatment produced the most significant impact concerning the control, improving yield by 19±1% (3 t ha-1), cob length 18±1%, cob diameter 22±3%, weight (16±2%) and corn kernels size (14±2%). We also find negative effects on yield, D2-T1 decreased crop yield around 16±1% (2.24 t ha-1). The results show a way to include this technique as a technique that can to increase or decrease corn yield. Keywords: Cob length; Maize; open field; Thousand kernel weight.